CORRELATION BETWEEN PERMEABILITY AND POROSITY WITH OTHER PROPERTIES OF CONCRETE - Al-lami, Mohammed (Journal of Applied Engineering Science, 2021)
Most of concrete properties such as strength, permeability, density and absorption are signiﬁcantly affected by the porosity of its internal microstructure. Many researchers studied the relationships between permeability, porosity and other properties of concrete, but in the author’s opinion, the subject still needs more researching works. The purpose of this research is to investigate the possible correlations between concrete porosity and permeability with other properties such as compressive strength, absorption and density. Helium Gas Pores meter was used to measure porosity and Nitrogen Gas Permeate device was used to measure permeability. The investigated variables were the aggregate to cement ratio (A/C) and water to cement ratio (W/C). Based on regression analysis of test results, mathematical relationships between tested properties were suggested. The higher correlations were observed for mixes with constant water to cement ratio and variable aggregate to cement ratio.